Accuracy of a composite event definition for hypoglycemia. Issue 5 (6th March 2019) - Min, Jea Young; Presley, Caroline A.; Wharton, Jennifer; Griffin, Marie R.; Greevy, Robert A.; Hung, Adriana M.; Chipman, Jonathan; Grijalva, Carlos G.; Hackstadt, Amber J.; Roumie, Christianne L.
Abstract: Purpose: To evaluate the accuracy of a composite definition for the identification of hypoglycemia events that used both administrative claims and laboratory data in a cohort of patients. Methods: We reviewed medical records in a sample of presumed hypoglycemia events among patients who received care at the Veterans Health Administration Tennessee Valley Healthcare System in 2001 to 2012. A hypoglycemia event was defined as a hospitalization or emergency department visit judged by the treating clinician to be due to hypoglycemia, or an outpatient laboratory or point‐of‐care blood glucose measurement <60 mg/dL. Based on medical record review, each event was classified as true positive (severe, documented symptomatic, documented asymptomatic) or false positive (probable symptomatic, not hypoglycemia). The positive predictive values (PPV) of the individual event types (hospitalization, emergency department, and outpatient) were estimated. Results: Of 2250 events identified through the composite definition, 321 events (15 hospitalizations, 103 emergency department visits, and 203 outpatient events) were reviewed. The PPVs were 80% for hospitalization events, 48% for emergency department events, and 96% for outpatient events. The emergency department definition included a nonspecific diagnosis code for diabetic complications which captured many false positive events. Excluding this code from the definition improved the PPV for emergency department events to 70% and missed one true event. Conclusions: Our composite definition for hypoglycemia performed moderately well in a cohort of Veterans. Further evaluation of the emergency department events may be needed.